2022
DOI: 10.3748/wjg.v28.i28.3706
|View full text |Cite
|
Sign up to set email alerts
|

Family-based Helicobacter pylori infection status and transmission pattern in central China, and its clinical implications for related disease prevention

Abstract: BACKGROUND Helicobacter pylori ( H. pylori ) has characteristics of family cluster infection; however, its family-based infection status, related factors, and transmission pattern in central China, a high-risk area for H. pylori infection and gastric cancer, have not been evaluated. We investigated family-based H. pylori infection in healthy households to understand its infection status, related factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 34 publications
2
4
1
Order By: Relevance
“… 30 One 2022 family-based H. pylori infection survey on 282 families (772 individuals) also reported that the household infection rate was 87.23% in central China. 31 The current work is in line with these studies and provides important evidence indicating that the clustering of infections within the same family was due to increased infection, not simply by chance. It also highlights the importance of implementing family-based H. pylori infection control and management in clinical practice.…”
Section: Discussionsupporting
confidence: 85%
“… 30 One 2022 family-based H. pylori infection survey on 282 families (772 individuals) also reported that the household infection rate was 87.23% in central China. 31 The current work is in line with these studies and provides important evidence indicating that the clustering of infections within the same family was due to increased infection, not simply by chance. It also highlights the importance of implementing family-based H. pylori infection control and management in clinical practice.…”
Section: Discussionsupporting
confidence: 85%
“…We found that the risk of HP infection increased with a family history of gastric disease. This finding is contrary to previous studies, which have suggested that a family history of gastric disease does not affect the infection rate [ 46 ]. This difference in findings may have arisen, as we excluded patients with gastric symptoms.…”
Section: Discussioncontrasting
confidence: 99%
“…The study investigated the prevalence of Hp-positive infections across different age groups. The results showed that the prevalence increased with age, particularly in the 0-40 age group, which is consistent with previous studies [10,20]. It seemed that the risk of Hp infection in the population was concentrated in children and young adults, thus, the study focused on analyzing Hp infection in minors.…”
Section: Discussionsupporting
confidence: 90%